Lexical understanding of basic colors according to the poems of Georgian symbolists - Feride Sanay (Genius Journals, 2022)
In the paper, we have analyzed such a semantic component from linguistic-cultural positions as the vocabulary of color in poetic language. Therefore, the main focus of the article is on understanding the words of the Georgian symbolists - the colors of the creative circle of the literary circle of the "Blues". Practical examples are given. By observing the works of Georgian symbolists, in the paper we tried to explain the meanings of color words according to specific verses, for this we had to quote excerpts from the verses frequently in order to present more specifically the function and meaning of color in a literary text. In fiction, the symbolic meanings of colors are generally not stable. The same color is sometimes subject to mutually exclusive explanations. In the poems of Georgian Symbolists, blue - mainly sadness, red - is the color of evil, war and aggression, while yellow is the color of sickness and death. In their poetry, the symbolic meaning of color is multifaceted, sometimes even different. It is true that bright sunshine is the color of nobility, and yellow is the color of life, joy, but this is when the color is in balance. Thus, each color expresses an appropriate event or feature (sadness, melancholy, heartache, beauty ...). The nature and abundance of the use of the color phenomenon depends on the author. The authors apply either color variation or colors are rarely realized in their works. Different colors, depending on the context, evoke both positive and negative emotions. Therefore, their readers' evaluation is also doubled. In the Georgian poetry of the beginning of the twentieth century, mainly white and black colors predominate. Then there are blue / blue / navy, yellow, red, green and the rest of the colors. The poetry of the "Rainbows" is full of distinctive colors, which intensifies the feeling, creates color, it is also a kind of poetic way of intuitive access. Color allows to present an unusual and at the same time, vague poetic face. Due to the specifics of a certain field of art, the subject gives his interpretation to this attitude and enriches it with new symbolic content. Thus, among the features that determine the individuality of writers, a certain place is occupied by the use of colors. The symbolism of color is so variable and multifaceted that over time its function has become diverse. It is therefore impossible to study its essence thoroughly. Although the content of the color symbols undergoes significant changes, from an interpretive point of view, the core of the color symbolism still remains unchanged. In poetry he deals with so many comprehensive issues that his understanding is sometimes different
Keywords: Color; Georgian Symbolists; Poetry; Rainbows